Determination of Sun Protection Factor and Antioxidant Properties of Cream Formulation of Kencur (Kaempferia galanga L) and Temu Kunci (Boesenbergia pandurata (Roxb.) Schlecht) Rhizomes Extract - Charisma, Shintia Lintang; Rahayu, Wiranti Sri; Wahyuingrum, Retno (Universitas Ahmad Dahlan, 2018)
Kencur (Kaempferia galanga, L.) rhizome contain ethyl-p-methoxycinnamate (EPMS) which has sunscreen properties. Temu kunci (Boesenbergia pandurata (Roxb) Schlecht) rhizome contains flavonoid and essential oils with oxidant radical scavenging properties. The aims of this study were to obtain the optimum physical properties of sunscreen and antioxidant cream and to compare the sun protection factor (SPF) values and antioxidant activity of kencur and temu kunci rhizomes extract before and after formulated.This research used Simplex Latice Design (SLD) model with 2 components of kencur extract and temu kunci extract. Based on the SLD model obtained optimum formula design, then the SPF values and antioxidant activity were studied by UV spectrophotometric method and DPPH method respectively.Based on SLD model obtained optimum formula that containing kencur : temu kunci extract 80%:20% (formula A) and 70%:30% (formula B). The SPF values of kencur extract, formula A and formula B were 4.505, 5.024 and 4.511 respectively. Antioxidant activity showed that the IC50 of formula A, formula B, temu kunci extract, BHT and Vitamin E were 109.15 µg/ml, 95.23 µg/ml, 10.20 µg/ml, 22.33 µg/ml and 8.78 µg/ml respectively.Cream formula A and formula B have optimum physical properties. The SPF value of the optimum formulations were higher than SPF value of kencur extract. Antioxidant activity of that combinations were lower than temu kunci extract, BHT and Vitamin E.